Degradation of the plaquemines sub-delta and relative sea-level in eastern Mississippi deltaic coast during late holocene. (31st October 2019) - Wang, Jiaze; Xu, Kehui; Bentley, Samuel J.; White, Crawford; Zhang, Xukai; Liu, Haoran
Abstract: The stratigraphic architecture of Plaquemines sub-delta lobe is identified from sedimentary cores and sub-bottom seismic data collected at Lower Breton Sound, Louisiana, USA. Four lithofacies were identified in cores from bottom to top: (1) organic-poor mud; (2) organic-poor silty sand; (3) massive mud; (4) organic-rich peat and root-rich soft mud. Overall, the lithofacies displays a typical progradational deltaic deposit at bottom with upward-coarsening feature, and then an upward-fining deposit overlying on top. Stratigraphic position of the organic-rich peat facies indicates that it is formed after the fluvial sediment source moves away from this region, and it is recognized as a termination of progradation of the Plaquemines sub-delta. Dated peat samples show that sub-delta progradation stops between 876 and 1384 yr AD, during which a 20–70 cm relative sea-level rise is detected. The geological framework reported in this study provides critical information for future modeling on river diversions. The stratigraphic architecture underlying Lower Breton Sound implicates that top three facies of root-rich soft mud, organic-rich peat and massive mud are likely to be eroded away before the development of new crevasse-splay or sub-delta, when sediment diversion is in operation. The deeper organic-poor silty sand lithofacies, however, can serve as a firm foundation to build new land. Highlights: High resolution stratigraphy of the Plaquemines sub-delta lobe is reported. Progradation of the Plaquemines sub-delta lobe stops during 876–1384 yr AD. A 20–70 cm relative sea-level rise is detected at Lower Breton Sound during 876–1384 yr AD.